Workload monotony, strain and non-contact injury incidence in professional football players - Delecroix, B.; Mccall, A.; Dawson, B.; Berthoin, S.; Dupont, G. (Science and Medicine in Football, 2019)
Objectives: The purpose of this study was to analyse the association of the workload monotony and workload strain with the injury incidence with professional football players taking part in European football competitions. Methods: A total of 130 elite football players, from 5 teams playing European competitions, have been followed during a season. The internal workload was calculated using the Session Rate of Perceived Exertion method and the injuries were recorded. The 4-weeks, 3-weeks, 2-weeks and 1-week monotony (mean workload divided by workload standard deviation) and strain (absolute workload multiplied by monotony) were calculated on a daily basis, using a rolling days method. Results: The 4-weeks monotony was related to injury incidence. The relative risk (RR) of injury is decreased with an increase in 4-weeks monotony (RR = 0.72, 95% confidence interval [CI] 0.58-0.90; P = 0.004). The injury incidence was related to the 4-weeks strain. The RR of injury is increased with an increase 4-weeks strain (RR = 1.50, 95% CI 1.14-1.97; P = 0.004). Conclusions: The links between a high 4-weeks monotony and the injury incidence, and the links between a high 4-weeks strain and the injury incidence indicate that monotony and strain were associated with injury incidence in elite football players and require to be monitored.